Management of untreatable ventricular arrhythmias during pharmacologic challenges with sodium channel blockers for suspected Brugada syndrome. Issue 2 (17th May 2017) - Poli, Stefano; Toniolo, Mauro; Maiani, Massimo; Zanuttini, Davide; Rebellato, Luca; Vendramin, Igor; Dametto, Ermanno; Bernardi, Guglielmo; Bassi, Flavio; Napolitano, Carlo; Livi, Ugolino; Proclemer, Alessandro
Abstract: Pharmacologic challenge with sodium channel blockers is part of the diagnostic workout in patients with suspected Brugada syndrome. The test is overall considered safe but both ajmaline and flecainide detain well known pro-arrhythmic properties. Moreover, the treatment of patients with life-threatening arrhythmias during these diagnostic procedures is not well defined. Current consensus guidelines suggest to adopt cautious protocols interrupting the sodium channel blockers as soon as any ECG alteration appears. Nevertheless, the risk of life-threatening arrhythmias persists, even adopting a safe and cautious protocol and in absence of major arrhythmic risk factors. The authors revise the main published case studies of sodium channel blockers challenge in adults and in children, and summarize three cases of untreatable ventricular arrhythmias discussing their management. In particular, the role of advanced cardiopulmonary resuscitation with extra-corporeal membrane oxygenation is stressed as it can reveal to be the only reliable lifesaving facility in prolonged cardiac arrest.